Identification, molecular characterization and relative incidence of begomoviruses infecting bean crops in northwestern Argentina: an update - Varela, Gonzalo Matías (2018)
Three begomoviruses were identified in bean crops in northwestern Argentina: Bean golden mosaic virus (BGMV), Tomato yellow spot virus (ToYSV) and Soybean blistering mosaic virus (SbBMV). Nucleic acid hybridization probes specific for these three begomoviruses were developed, and used to assay field samples. As some of the analysed begomovirus-infected samples did not react with any of the specific probes, we suspected that other viruses were present. DNA of two of these samples P160, and PRCA4, was amplified by rolling circle amplification (RCA), and cloned. Four clones were sequenced by primer walking and nucleotide comparisons established that clones P160SacI and P160ApaI shared 93 and 94% nucleotide identity with DNA-A and DNA-B of Sida golden mosaic Brazil virus (SiGMBRV), respectively. Clone PRCA4.6PstI had 94% sequence identity with DNA-A of Tomato mottle wrinkle virus (ToMoWV), and clone PRCA4.17PstI exhibited 95% nucleotide sequence identity with the DNA-A of Tomato yellow vein streak virus (ToYVS), indicating a mixed infection. Specific probes were designed using part of the common region of the viral genome of the newly identified begomoviruses and were used to test bean samples during the 2014–2016 growing seasons. ToMoWV was the most frequently detected virus. The incidence of the three previously characterized begomoviruses (BGMV, SbBMV and ToYSV) was also assessed, and BGMV was found to exhibit the highest incidence. The diversity of begomoviruses found in bean in our country is remarkable, since, six different species have been detected up to the present.